Impact of Emotional Harassment on Firm’s Value - Choi, Yun Hyeong; Park, Hee Jin; Choi, Seong-jin (Frontiers in Psychology, 2018)
The activities and consequences of workplace bullying and harassment have been widely explored in the literature but mainly studied within the scope of individuals or at the team level. Taking a holistic approach, we associate the concept of bullying with firm-level performance as well as stakeholders’ responses in the market. In this paper, we examine whether and how market investors react to the news of corporate harassment by top officials of publicly listed firms in Korea. Using a standard event study methodology and multiple regression analysis with matched sample, we find significantly negative stock price reactions to news of corporate bullying. We also find that the impact is more salient if emotional bullying is involved and discuss both the theoretical and practical implications of these findings.